ASSESSING GROUNDWATER QUALITY IN NORTH JAKARTA: A STATISTICAL APPROACH - Yureana Wijayanti; Riana Ayu Kusumadewi; Nicholas Albert Wijaya; Lisma Safitri; Risky Ayu Kristanti (Universitas Trisakti, 2025)
Aims: This study investigates the groundwater quality in North Jakarta. Methodology and results: The groundwater data from thirty-one sampling sites were analyzed for physical and chemical parameters such as total dissolved solids (TDS), pH, turbidity, nitrate (NO3), sulfate (SO4), chloride (Cl), manganese (Mn), fluoride (F), and iron (Fe). Principal Component Analysis (PCA) and Spearman’s correlation matrix were utilized to evaluate the contamination sources. Conclusion, significance, and impact study: The findings reveal significant variability in chloride and total dissolved solids (TDS) concentrations, while fluoride levels remained stable. Strong correlations were found between TDS and chloride, as well as, turbidity and iron, suggesting contamination from seawater intrusion and industrial activities. PCA identified four key components explaining 77% of the total variance. The first component, dominated by TDS, turbidity, iron, and chlorine, indicates ongoing seawater infiltration in the coastal aquifer. The second component, associated with turbidity, nitrate, and fluoride, indicates contamination from human activities. This study shows the value of multivariate statistical techniques like PCA, in assessing groundwater quality. The correlation matrix further confirms the influence of seawater on groundwater salinity and the presence of heavy metals, possibly due to soil disturbance. Moreover, there is an influence of geological and geographical factors, particularly the excessive groundwater extraction leading to seawater intrusion and groundwater quality deterioration.